Pengaruh Kualitas Produk, Brand Image, dan Komunikasi Pemasaran Terhadap Keputusan Pembelian Rumah Glory Royal Residence di Kota Batam: Pengaruh Kualitas Produk, Brand Image, dan Komunikasi Pemasaran Terhadap Keputusan Pembelian Rumah Glory Royal Residence di Kota Batam - Ratna Sari; Saputra, Asron (LPPM Universitas Putera Batam, 2025)
This study investigates the influence of product quality, brand image, and marketing communication on purchasing decisions for houses at Glory Royal Residence, Batam City. Using a quantitative approach, the research involved 110 respondents selected through simple random sampling based on the Slovin formula. Data were analyzed using descriptive statistical tests, data quality tests, classical assumption tests, multiple linear regression analysis, and hypothesis testing. Results show that product quality, brand image, and marketing communication collectively explain 70.6% of the variation in purchasing decisions, with brand image contributing the most significant effect (32.9%), followed by product quality (31.8%) and marketing communication (23.2%). Hypothesis testing confirms that all variables have a positive and significant impact on purchasing decisions, both partially and simultaneously. The findings emphasize the need to strengthen brand image, improve product quality, and enhance marketing communication strategies to boost consumer purchasing decisions effectively.